Barba i Bjørneboe: Listy pełne marzeń - Ewa Partyga (Pamiętnik Teatralny, 2017)
The article focuses on selected motifs of the correspondence between Eugenio Barba and Jens Bjørneboe in 1962–1964. At the time, the artists shared a plan to invigorate the Norwegian theatre life by founding a professional journal and an experimental theatre company. One of the most significant impulses in their quest had been Barba’s Polish experience and his reflexion on the history and contemporary development of Polish theatre that he summed up in the essay first published in Vinduet in 1963, which we now republish in Pamiętnik Teatralny in Polish translation.